Bluecoated terror: Jim Crow New Orleans and the roots of modern police brutality - Adler, Jeffrey S. (University of California Press, 2024)
"In Bluecoated Terror, Jeffrey S. Adler draws on rich archival accounts to show, in narrative detail, how racialized police brutality is part of a larger system of state oppression with roots in the early twentieth-century South, particularly New Orleans. Wide racial differentials in the use of lethal force and beatings during arrest and interrogation emerged in the 1930s and 1940s. Adler explains how race control and crime control blended and blurred during this era, when police officers and criminal justice officials began to justify systemic violence against Black people as a crucial-and legal-tool for maintaining law and order. Bluecoated Terror explores both the rise of these law-enforcement trends and their chilling resilience, providing critical context for recent horrific police abuses as the ghost of Jim Crow law enforcement continues to haunt the nation"--